Managing people - Rowley, Chris (Henry Stewart Talks, 2010)
What is People Management and HRM?, Employee Resourcing, Employee Rewards, Employee Development, Employee Relations, Development & Traditions in People Management, Welfare & Paternalism, Administrative & Bureaucratic, Development, What are any Differences from Past forms of People Management and Personnel Management?, Strategy, Rhetoric & Reality in the area of people management, Context for people management, Organisational, HR function and practitioners, The Future for people management and HRM